Analysis Of Product Innovation and Promotion in Improving Competitiveness In Opak Ujo Khas Conggeang UMKM - Naisa, Fia Indriani Rahadatul; Khairunisa, Nisrina; Wianda, Nur Riska; Padillah, Rizky Nur; Septiani, Sri; Gumelar, Rizky; Nurhandayani, Sri Rahayu (SINTESA, 2024)
Opak Ujo UMKM was established in 2000 and has maintained its existence until now. Despite its great potential, Opak Ujo still faces significant challenges in increasing its competitiveness, both locally and nationally. These challenges include competition with manufacturers of similar products, limited innovation in product development, and limited effective promotional strategies. Therefore, the purpose of this study is to determine the product innovation and promotion carried out by Opak Ujo UMKM in an effort to increase competitiveness. The method used in this study is a qualitative analysis method by describing the results of the study through descriptive narratives. The results of this study are that product innovation and promotion carried out by Opak Ujo UMKM can increase competitiveness, but not significantly due to several obstacles such as the lack of continuous innovation and intensive promotion through social media. With continuous product innovation and the use of social media as a means of intensive promotion, it will increase competitiveness with UMKM that produce similar products